Serum testosterone and lipids in relation to sexual dysfunction in males with metabolic syndrome and type 2 diabetes mellitus (2010)
Low serum testosterone is associated with insulin resistance, metabolic syndrome (case 1), type 2 diabetes mellitus (case 2), and cardiovascular disease. This study aims at identifying possible alterations in circulating testosterone and their relationship with plasma lipids in case1 and case2. Ninety-two male subjects were recruited in this prospective, cross-sectional study from two major hospitals in Ibadan and environs, Nigeria. Demographic, sexual and anthropometric characteristics were obtained from questionnaires by use of standard methods. Blood samples (10 ml) were obtained for determination of glucose, total cholesterol, triglycerides and high density lipoprotein by enzymatic methods while low density lipoprotein was calculated. Testosterone was analysed by Enzyme Immunoassay (Fortress Diagnostics, UK.). SPSS software version 16.0 was used for statistical analysis to find associations and relationships. Significantly lower concentrations of testosterone and high density lipoprotein, but higher concentrations of glucose in case 1 and 2 groups were observed compared with controls (p<0.05). Testosterone correlated positively with libido and nocturnal/early morning erection but inversely with erectile dysfunction only in case 2 (p<0.05). Deficient glucose uptake by the pituitary and the gonads and low circulating high density lipoprotein, consequence of insulin resistance could lead to hypogonadism. Dietary modulation and exercise may therefore be beneficial.